Heat - Grant, Donna (Grant, Donna. Dark kings novel, 2018)
"Ever since MI5 agent Esther woke to discover her mind taken over with magic, she feels like a stranger to herself. She looks to a notorious dragon, one who has the power to help her find her memory. But as she and Nikolai come closer to discovering what really happened to her, a dangerous passion ignites between them. Can this lone Dragon King help the woman hes grown to love to uncover the truth about her past--or will a deep and fiery danger tear them both apart?"--Amazon.com.